2018
DOI: 10.1142/s1088424618500967
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated derivatives of meso-(aminophenyl)porphyrins: Synthesis and some transformation

Abstract: Condensation of amino groups in 5-(4-aminophenyl)-10,15,20-triphenylporphyrin and 5,10,15,20-tetrakis(4-aminophenyl)porphyrin with pentafluorobenzaldehyde resulted in corresponding Schiff bases and was shown to be a convenient route for the preparation of fluorinated porphyrin derivatives. Compounds thus obtained were easily transformed into the corresponding amines using sodium borohydride. Fluorinated carboranyl porphyrins were prepared via the nucleophilic substitution of the para-fluorine atom of pentafluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…49,50 Similar reactions are usually employed for the functionalization of macrocyclic compounds such as porphyrins, chlorins, phthalocyanines and BODIPYs. 15,37,[51][52][53] It was found that the reactions of BODIPYs 4, 5 and 7 with the corresponding mercaptocarboranes proceeded efficiently for 1 h in DMF in the presence of NaOAc for compounds 4 and 5 and in the presence of K 2 CO 3 for compound 7 providing the desired BODIPYs 8-10 decorated with three carborane clusters in 70-81% yields (Scheme 1).…”
Section: Synthesismentioning
confidence: 99%
“…49,50 Similar reactions are usually employed for the functionalization of macrocyclic compounds such as porphyrins, chlorins, phthalocyanines and BODIPYs. 15,37,[51][52][53] It was found that the reactions of BODIPYs 4, 5 and 7 with the corresponding mercaptocarboranes proceeded efficiently for 1 h in DMF in the presence of NaOAc for compounds 4 and 5 and in the presence of K 2 CO 3 for compound 7 providing the desired BODIPYs 8-10 decorated with three carborane clusters in 70-81% yields (Scheme 1).…”
Section: Synthesismentioning
confidence: 99%
“…To continue our ongoing efforts on the preparation of porphyrin-based photosensitizers [1720], we present herein the synthesis of maleimide-subtituted porphyrins and chlorins based on 5,10,15,20-tetrakis(pentafluorophenyl)porphyrin ( 1 ) as the starting compound. The presence of fluorine atoms on the four phenyl rings at the meso -positions of the porphyrin structure can make a strong influence on the hydrophobic interactions and lipophilicity, metabolic stability, thus modulating the biological efficiency of the photosensitizing agents [2122].…”
Section: Introductionmentioning
confidence: 99%